Genotypic variation in parasite avoidance behaviour and other mechanistic, nonlinear components of transmission. Issue 1915 (20th November 2019) - Strauss, Alexander T.; Hite, Jessica L.; Civitello, David J.; Shocket, Marta S.; Cáceres, Carla E.; Hall, Spencer R.
Abstract : Traditional epidemiological models assume that transmission increases proportionally to the density of parasites. However, empirical data frequently contradict this assumption. General yet mechanistic models can explain why transmission depends nonlinearly on parasite density and thereby identify potential defensive strategies of hosts. For example, hosts could decrease their exposure rates at higher parasite densities (via behavioural avoidance) or decrease their per-parasite susceptibility when encountering more parasites (e.g. via stronger immune responses). To illustrate, we fitted mechanistic transmission models to 19 genotypes of Daphnia dentifera hosts over gradients of the trophically acquired parasite, Metschnikowia bicuspidata . Exposure rate (foraging, F ) frequently decreased with parasite density ( Z ), and per-parasite susceptibility ( U ) frequently decreased with parasite encounters ( F × Z ). Consequently, infection rates ( F × U × Z ) often peaked at intermediate parasite densities. Moreover, host genotypes varied substantially in these responses. Exposure rates remained constant for some genotypes but decreased sensitively with parasite density for others (up to 78%). Furthermore, genotypes with more sensitive foraging/exposure also foraged faster in the absence of parasites (suggesting 'fast and sensitive' versus 'slow and steady' strategies). These relationships suggest that high densities of parasites can inhibit transmission by decreasing exposure rates and/or per-parasite susceptibility, and identify several intriguing axes for the evolution of host defence.